IP address allocation protocols in vehicular ad hoc networks - Ajaz, Farhana; Naseem, Mohd; Ahamad, Gulfam (International journal of communication systems, 2023)
Summary In vehicular ad hoc networks (VANETs), communication takes place between vehicles to vehicles, the vehicles to the road side units, and vice‐versa. The basic purpose of these communications is to share and exchange tremendous amount of data and information. For efficient information sharing, a systematic and structured connection establishment algorithm is needed. In VANETs, each connected node of the network need to be assigned a unique address. Hence, an algorithm is needed for the proper assignment of unique address to all nodes in the network. This paper explains different types of IP address protocols in VANETs. We have also explained advantage and disadvantage of existing IP address allocation protocols in VANETs. In vehicular ad hoc networks (VANETs), communication takes place between vehicles to vehicles, the vehicles to the road side units, and vice versa. Hence, an algorithm is needed for the proper assignment of unique address to all nodes in the network. This paper explains different types of address based routing protocols in VANETs. We have also explained various advantages and disadvantages of existing address based routing protocols in VANETs.